A Method for Retrieving Vertical Ozone Profiles from Limb Scattered Measurements - 汪自军 陈圣波 杨春燕 金丽华 (Acta meteorologica Sinica, 2011)
A two-step method is employed in this study to retrieve vertical ozone profiles using scattered measure- ments from the limb of the atmosphere. The combination of the Differential Optical Absorption Spectroscopy （DOAS） and the Multiplicative Algebraic Reconstruction Technique （MART） is proposed. First, the limb radiance, measured over a range of tangent heights, is processed using the DOAS technique to recover the effective column densities of atmospheric ozone. Second, these effective column densities along the lines of sight （LOSs） are inverted using the MART coupled with a forward model SCIATRAN （radiative transfer model for SCIAMACHY） to derive the ozone profiles. This method is applied to Optical Spectrograph and Infra Red Imager System （OSIRIS） radiance, using the wavelength windows 571–617 nm. Vertical ozone profiles between 10 and 48 km are derived with a vertical resolution of 1 km. The results illustrate a good agreement with the cloud-free coincident SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY （SCIAMACHY） ozone measurements, with deviations less than ± 10% （ ± 5% for altitudes from 17 to 47 km）. Furthermore, sensitivities of retrieved ozone to aerosol, cloud parameters and NO 2 concentration are also investigated.